2018
DOI: 10.1590/0037-8682-0080-2017
|View full text |Cite
|
Sign up to set email alerts
|

Clonal relationships, antimicrobial susceptibilities, and molecular characterization of extended-spectrum beta-lactamase-producing Escherichia coli isolates from urinary tract infections and fecal samples in Southeast Iran

Abstract: The high rates of antibacterial-resistant and MDR isolates are quite important since these strains can act as source of resistant bacteria that can be spread in the community. Controlling antibiotic use, against inappropriate use and abuse, in the community and continuous surveillance of emerging resistance traits are critical to controlling the spread of resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 30 publications
3
11
4
Order By: Relevance
“…38 This finding was inconsistent with our results revealing 82.9%, 40%, and 2.9% of isolates harbored bla CTX-M , bla TEM , and bla SHV , respectively. Based on our findings, the occurrence of bla SHV gene was lower than that reported in Iran 31,37,39 and Portugal, 38 but it was similar to that reported in Turkey. 5 Despite the relative agreement on the higher incidence of ESBLs genes among UPECs, a discrepancy in the prevalence of ESBL producers was observed over different regions, which is probably due to differences in geographical regions, infection control policy, and sample source.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…38 This finding was inconsistent with our results revealing 82.9%, 40%, and 2.9% of isolates harbored bla CTX-M , bla TEM , and bla SHV , respectively. Based on our findings, the occurrence of bla SHV gene was lower than that reported in Iran 31,37,39 and Portugal, 38 but it was similar to that reported in Turkey. 5 Despite the relative agreement on the higher incidence of ESBLs genes among UPECs, a discrepancy in the prevalence of ESBL producers was observed over different regions, which is probably due to differences in geographical regions, infection control policy, and sample source.…”
Section: Discussionsupporting
confidence: 82%
“…According to some previous studies, the bla CTX-M is the most frequent beta-lactamase in UPEC isolates. 27,31,37 This finding confirms the importance of the spread of bla CTX-M types in ESBL production.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Similarly, in a study from Spain, 24 a significant association was found between UTIs due to ESBL-positive E. coli and male sex. In contrast, in another study in Iran, 23 the production of ESBLs in UPEC isolates of different gender was not significantly different.…”
Section: Esbl-producing Upeccontrasting
confidence: 58%
“…As a result, it can be said that common β-lactam drugs could not effect at least one-third of these UPECs. In another study 23 on E. coli isolates from UTIs in Kerman, Iran, 41% of outpatients had ESBL-positive isolates. A somewhat similar (40%) rate of ESBL producers was reported in UPECs in a study in Pakistan.…”
Section: Esbl-producing Upecmentioning
confidence: 95%